Animation and its psychological implications for children (Journal of Humanities and Social Sciences Research, 2023)
The aim of the current research is to reveal the psychological repercussions of animation and its impact on children, by introducing the childhood stage and its importance and defining the rights and duties of the child, then moving on to revealing the nature of animation, its objectives, benefits, features and criteria for presentation, in addition to the psychological pros and cons of animation programs on the child's personality. The importance of the research stems from the importance of animation as a social and cultural product that leaves its positive and negative effects on the development of the child and the formation of his personality. Society as a whole, when realizing the psychological effects of animation programs, parents will become more aware and selective about programs that are appropriate for their children and that help them in their healthy development. The research followed the descriptive analytical approach, and concluded that animation programs contribute greatly to building the child’s psychological personality, raising him and changing his behavior, and that interest in raising and educating the child necessarily leads to interest in his programs shown on television, so it was necessary to observe the criteria for displaying animation programs and be careful To apply it to all content and topics directed to children on the screen.